La medicina di base e la psichiatria - Di Stefano, Claudio (Il sogno della farfalla, 2018)
Most people affected by psychiatric diseases prefer to be visited by their own general practitioner. Therefore there is a worldwide consensus about the central role the GP plays in the prevention and early diagnosis of psychiatric diseases. The aim of this article is to look into the peculiarities and skills required in carrying out this highly responsible task. Historically speaking, the author stresses that in Italy the creation of the National Health Service and the rise of the general practitioner that followed, on the one hand, and the closing of the mental hospitals on the other hand were contemporaneous events that however did not promote a cooperation between general medicine and psychiatric departments. A result of this lack of cooperation is the delay experienced in sending psychiatric patients from the GP to the specialist. Nevertheless psychic patients prefer to be visited by their own GP for many reasons. First of all: the effect of not being stigmatized, therapeutic continuity, being acquainted with one’s home, social and at times working environment, free admittance, the therapeutic alliance and empathy are the strong points of every GP. But they are not enough, because the GP needs a clinical attitude and a modern theory of the mind, such as the birth theory proposed by Massimo Fagioli, in order to make a differential diagnosis between somatic and psychiatric diseases. Being prepared to listen can be a true psychotherapeutic attitude towards patients affected by psychiatric illnesses.